Faktor-Faktor Yang Mempengaruhi Produksi Pala Di Kecamatan Manganitu Kabupaten Kepulauan Sangihe - Yustin Tarimakase; Paulus A. Pangemanan; Jenny Baroleh; Gene H.M. Kapantow (Universitas Sam Ratulangi, 2014)
ABSTRACTYustin Tarimakase. The factors that influence the production of nutmeg in Manganitu Sub District (Under guidance of Paulus A. Pangemanan as a cahirman Jenny Baroleh and Gene H. M. Kapantow as members).The objective of this research is to determine tha factor that influence the production of nutmeg in Manganitu Sub District, Sangihe Islands. This research uses survey methods and Primary data obtained from questioner and interview with nutmeg farmers and secondary data from related department such as agriculture, animal, husbandry, estate plantation, and forestry service of Sangihe Island Regency, Manganitu sub District office and Sangihe Islands Statistic Central Service.This study analyzed using multiple regression by calculating the factors that influence behavior of farmers in production such as land, labor, capital and farmers behavior (dummy).The result of this research showed that was by R value or determination coefficient was 73,89 the remaining 26,2 %. The result of regression analysis from the formula Y = 4,0 + 34,9 X1 – 6,87 X2 + 0,0004 X3 + 5,32 X4.Effect of land to nutmeg production (X1) was 34,9 of means that the increase of one unit of land will be followed by the increase of 34,9 unit of production. The effect of labor to nutmeg production (X2) was – 6,87 means that the increase of one unit of labor will be followed by the decrease of 6,87 unit of nutmeg production.The effect of capital to nutmeg production (X3) was 0,00004 means that the increase of one unit of capital will be followed by the increase of 0,0004 unit of production.The effect of farmer behavior to nutmeg production (X4) was 5,34 means that the increase of one unit of farmer behavior will be followed by the increase of 5,34 unit production